2014
DOI: 10.1016/j.seizure.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for remote seizure development in patients with cerebral vein and dural sinus thrombosis

Abstract: Our results demonstrate that seizure development in the acute phase is the most significant factor for development of remote seizure. Parenchymal lesions in the supratentorial area were also found to be associated with both acute and remote seizures. However, no factor was predictive of acute or remote seizures in a multivariate analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 13 publications
2
45
2
1
Order By: Relevance
“…However, in other studies, generalized seizures are reported to have a higher frequency, particularly in severe cases of CVST who underwent thrombolysis …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, in other studies, generalized seizures are reported to have a higher frequency, particularly in severe cases of CVST who underwent thrombolysis …”
Section: Discussionmentioning
confidence: 80%
“…The incidence rate of ASS has a widely varied range in different studies. ASS in CVST are reported in 6.9–76% of patients, with the higher incidence in severe CVST cases (60%) and peripartum CVST (76%) . The risk of PCE is low compared with the high rate of ASS, and is reported in about 4–16% of patients in different studies that followed patients between 12 months to a mean of 77.8 months .…”
Section: Discussionmentioning
confidence: 99%
“…135 Supratentorial lesion was a predictor of seizures in several studies. 52,135,136 Seizures are common in CVT and may be a cause of early death. This was the reason to upgrade the strength of the recommendation from uncertain to weak, which was formally achieved by a unanimous consensus through a nominal group technique.…”
Section: (Recommendations)mentioning
confidence: 99%
“…[5] A further study performed on 94 patients by Davoudi et al found that 19.1% of patients experienced presenting seizures and 21.3 % of patients had early seizures in the 2. week after confirmation of the CVST diagnosis. [19] In the study of Kalita et al 46.7% of patients with CVST had presenting seizures and 4.4% had early seizures, which were independently related to supratentorial lesion. [21] The results of all these studies support our findings: all of the patients with seizures had supratentorial lesions (mainly with a hemorrhagic component), 2 patients had motor weakness, and 2 patients were pregnant.…”
Section: Discussionmentioning
confidence: 93%
“…[4,[17][18][19] Patients with CVST are significantly more at risk to develop a seizure than patients with hemorrhage or ischemic stroke. [17] Status epilepticus has a poor prognosis and is one of the main causes of early death in CVST.…”
Section: Discussionmentioning
confidence: 99%